2010
DOI: 10.1016/j.bcmd.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

TEThered to Runx: Novel binding partners for runx factors

Abstract: RUNX transcription factors reside in the nuclear matrix where they integrate numerous signaling pathways to regulate gene expression and affect tissue development, regeneration, and tumorigenesis. An affinity purification and proteomic experiment was performed to identify novel Runx2 binding partners. The interactions between Runx2 and two nuclear factors identified in this screen, Ddx5 and CoAA, were previously described. Co-activator activator (CoAA) bound the DNA binding domain of Runx2 and prevented Runx-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
(57 reference statements)
1
23
1
Order By: Relevance
“…We recently reported that EWSR1 and EWS‐FLI interact with the Runt domains of Runx2 and Runx1 [Li et al, 2010]. To determine the region of EWS‐FLI that binds Runx2, GST pulldown assays were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that EWSR1 and EWS‐FLI interact with the Runt domains of Runx2 and Runx1 [Li et al, 2010]. To determine the region of EWS‐FLI that binds Runx2, GST pulldown assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Runx2 is highly expressed in osteosarcomas, which are tumors derived from cells of a mature osteoblast phenotype, and is also easily detected in tumors that metastasize to the skeleton. We recently showed that Runx2 and Runx1 associate with TET family members, EWSR1, EWS‐FLI, and FUS, but the nature of those interactions remained unresolved [Li et al, 2010].…”
mentioning
confidence: 99%
“…It has been reported that Runx2 is a direct phosphorylation target for PKA (22); nevertheless, increases in Runx2 phosphorylation were not detected in either control or knockdown cells (data not shown). Previous studies have also indicated that the transcriptional activity of Runx2 can be modulated by binding to other nuclear proteins, including transcriptional coactivators, corepressors, and other transcription factors (23)(24)(25). As examples of the latter with relevance to osteogenesis, the Foxo1 protein was found to interact directly with Runx2, and Atf4 could indirectly associate with Runx2 in MC3T3-E1 cells to regulate osteocalcin gene expression (26 -29).…”
Section: Loss Of Prkar1a Suppressed Runx2-mediated Transcriptionmentioning
confidence: 92%
“…Recently, FUS was also shown to affect the transcription of RNA Pol III (Tan & Manley, 2010). Additionally, FUS affects gene expression by acting as co-regulator of several transcription factors, including nuclear hormone receptors (Powers et al, 1998), Spi-1/PU.1 (Hallier et al, 1998), NF-κB (Uranishi et al, 2001), and RUNX transcription factors (Li et al, 2010). The involvement of FUS in RNA splicing by binding splicing regulator or pre-mRNA was widely investigated as well (Sama et al, 2014).…”
Section: Tdp-43 and Fus: A Perspective Into Neurobiology And Nuclementioning
confidence: 99%